Fathers’ Experiences in Providing Kangaroo Mother Care for Premature Infants - Natalia Damaiyanti Putri Raden; Makrina Sedista Manggul; Paskalinda Maria Yosefa Bandur (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Kangaroo Mother Care (KMC) is traditionally performed by mothers, while fathers’ involvement often remains overlooked. Understanding fathers’ experiences is essential to promote their participation and strengthen their role in caring for premature infants. This study aimed to explore fathers’ lived experiences and inner perceptions regarding their involvement in providing Kangaroo Mother Care for premature infants, and to generate evidence supporting the promotion of father-led KMC as part of shared parenting. This qualitative study employed a descriptive phenomenological approach. Participants were selected using purposive sampling. Data were collected through in-depth interviews and direct observation, and analyzed using Colaizzi’s method. Six major themes emerged: (1) fathers’ awareness and knowledge of KMC; (2) fathers’ motivations and expectations; (3) emotional experiences during KMC; (4) strengthening of the paternal role through KMC; (5) barriers and challenges to father involvement; and (6) strategies and support needed to enhance fathers’ participation. In conclusion, fathers’ engagement in KMC enhances emotional bonding with their infants and reinforces their caregiving role. However, involvement is hindered by privacy concerns, gender role norms, and limited hospital facilities. Institutional policies and healthcare provider support are needed to encourage father participation and create a father-friendly care environment to optimize KMC implementation.Keywords: Kangaroo Mother Care; fathers; premature infants; paternal involvement